2006
DOI: 10.5194/acp-6-267-2006
|View full text |Cite
|
Sign up to set email alerts
|

Observation of mesospheric air inside the arctic stratospheric polar vortex in early 2003

Abstract: Abstract. During several balloon flights inside the Arctic polar vortex in early 2003, unusual trace gas distributions were observed, which indicate a strong influence of mesospheric air in the stratosphere. The tuneable diode laser (TDL) instrument SPIRALE (Spectroscopie Infra-Rouge par Absorption de Lasers Embarqués) measured unusually high CO values (up to 600 ppb) on 27 January at about 30 km altitude. The cryosampler BONBON sampled air masses with very high molecular Hydrogen, extremely low SF 6 and enhan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 50 publications
15
82
2
Order By: Relevance
“…They could have been caused by biomass burning from wildfires occurring over western Canada during the observation period. Lowest values of CO in the stratosphere are of the order of 10-20 ppb, in agreement with expected steady-state values (Toon et al, 1999;Engel et al, 2006b). AC-3, which was measured after AC-2 shows an increase in CO mixing ratios above 20 km, which is most probably due to the longer storage time, resulting in more diffusive mixing with remaining fill gas.…”
Section: Timmins 2015supporting
confidence: 70%
See 2 more Smart Citations
“…They could have been caused by biomass burning from wildfires occurring over western Canada during the observation period. Lowest values of CO in the stratosphere are of the order of 10-20 ppb, in agreement with expected steady-state values (Toon et al, 1999;Engel et al, 2006b). AC-3, which was measured after AC-2 shows an increase in CO mixing ratios above 20 km, which is most probably due to the longer storage time, resulting in more diffusive mixing with remaining fill gas.…”
Section: Timmins 2015supporting
confidence: 70%
“…On the other hand, the PG has much higher CO (about 1400 ppb) in order to allow a clear distinction from both tropospheric and stratospheric air. In particular, stratospheric air has much lower CO mixing ratios, which are on the order of 20 ppb (Engel et al, 2006b;Toon et al, 1999). Our measurements showed a gradual decrease of CO values from the high FG values to the significantly lower stratospheric mixing ratios.…”
Section: Correction Of Mixing Ratios For Mixing Betweenmentioning
confidence: 64%
See 1 more Smart Citation
“…For this purpose, G is defined in a convenient way as an Inverse Gaussian Distribution (IG) in terms of the mean age G and the width D, used in many different fields [e.g., Chikara and Folks, 1989;Seshadri, 1999]: [34] For the parameterization of the TTD, we apply G 2 /D = 0.7 as suggested by Hall and Plumb [1994] and confirmed by Engel et al [2002]. To prove that the initial mean age field is close to reality, a comparison is made with mean age profiles, derived from balloon-born measurements of CO 2 and SF 6 performed at mid-and high latitudes [Engel et al, 2002[Engel et al, , 2006b]. The good agreement between these profiles and the model profiles derived from the initial stratospheric mean age distribution illustrates the good quality of the KASIMA tracer fields (see Figure 2).…”
Section: Construction Of Initial Tracer Fieldsmentioning
confidence: 99%
“…During winter, dry air from the mesosphere descends into the stratosphere through the polar vortex, as modelled by Le Texier et al (1988) and observed by e.g. Lahoz et al (1994); Aellig et al (1996); Plumb et al (2002); Engel et al (2006).…”
Section: Introductionmentioning
confidence: 99%